Optimization of slow sand filtration for the raw municipal wastewater treatment by using the blood cockle (anadara granosa) shell as an alternative filter media through the response surface methodology - Fitriani, Nurina; Ni’matuzahroh2, Ni’matuzahroh; O’Marga, Timothy Tjahja Nugraha; Radin Mohamed, Radin Maya Saphira; Imron, Muhammad Fauzul; Isnadina, Dwi Ratri Mitha; Soedjono, Eddy Setiadi (2022)
This research aimed to investigate the optimum conditions of slow sand filter (SSF) media modification by using ground Anadara granosa shell waste and the effect of the ripening period on the total coliform (TC) removal efficiency. The response surface methodology with the central composite design was conducted with three factors, namely, seeding time (2–3 weeks), running time (0–20 days), type of SSF media (i.e., river sand, A. granosa shell, and their combination), as independent variables. The results showed that the ripening period factor interacted insignificantly by improving the TC removal efficiency due to short ripening time (p > 0.05). The optimum conditions of the SSF to achieve maximum TC removal efficiency (99.70 ± 21.50%) were as follows: combination media of river sand and ground A. granosa shell waste, 2.8 weeks (20 days) of ripening period, and 20 days of operation. In conclusion, the optimum operating parameters of the slow sand filter revealed that the combination of river sand and A. granosa shell as well as prolonged ripening and running times could increase the removal efficiency of TC. Hence, the A. granosa shell has good application potential as filter media to remove TC from the municipal wastewater.